Hospital-Acquired Conditions Reduction Program, Patient Safety, and Magnet Designation in the United States. Issue 8 (December 2021) - Hamadi, Hanadi; Borkar, Shalmali R.; Moody, LaRee; Tafili, Aurora; Wilkes, J. Scott; Moreno Franco, Pablo; McCaughey, Deirdre; Spaulding, Aaron
Abstract : Objective: The aim of the study was to investigate the association between hospitals' nursing excellence accreditation and patient safety performance—measured by the Hospital-Acquired Conditions Reduction Program (HACRP). Methods: We linked data from the American Nursing Credentialing Center Magnet Recognition Program, Centers for Medicare and Medicaid Services HACRP, and the American Hospital Association annual survey from 2014 to 2016. We constrained the analysis to hospitals participating in Centers for Medicare and Medicaid Services' HACRP and deployed propensity score matching models to calculate the coefficients for our HACRP patient safety measures. These measures consisted of ( a ) patient safety indicator 90, ( b ) hospital-associated infection measures, and ( c ) total HAC scores. In addition, we used propensity score matching to assess HACRP scores between hospitals achieving Magnet recognition in the past 2 versus longer and within the past 5 years versus longer. Results: Our primary findings indicate that Magnet hospitals have an increased likelihood of experiencing lower patient safety indicator 90 scores, higher catheter-associated urinary tract infection and surgical site infection scores, and no different total HAC scores. Finally, when examining the impact of Magnet tenure, our analysis revealed that there were no differences in Magnet tenure. Conclusions: Results indicate that the processes, procedures, and educational aspects associated with Magnet recognition seem to provide important improvements associated with care that is controlled by nursing practice. However, because these improvements do not differ when comparing total HAC scores nor Magnet hospitals with different tenure, there are likely opportunities for Magnet hospitals to continue process improvements focused on HACRP scores.